2014
DOI: 10.1016/j.irfa.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

European integration and corporate financing

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThis paper explores the importance of supply of capital for corporate financing. To identify this relation, we examine the impact of two exogenous events, entry to the EU and the adoption of Euro, which caused shifts in equity and credit markets during European integration.Following membership to EU, which eased access to equity capital, firms increase equity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
(114 reference statements)
2
3
0
Order By: Relevance
“…When looking instead at firms based outside the Euro area, we still observe a decrease in the use of new external equity during the crisis, but the difference between the two periods is much less pronounced. Again, these findings are in line with those reported in Muradoǧlu et al (2014): when their country of incorporation joins the European Union, companies increase the use of external equity. Then, when they also adopt the European common currency, they experience an increase in debt capacity, and gradually increase their use of leverage.…”
Section: Analysis Of Capital Structure: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When looking instead at firms based outside the Euro area, we still observe a decrease in the use of new external equity during the crisis, but the difference between the two periods is much less pronounced. Again, these findings are in line with those reported in Muradoǧlu et al (2014): when their country of incorporation joins the European Union, companies increase the use of external equity. Then, when they also adopt the European common currency, they experience an increase in debt capacity, and gradually increase their use of leverage.…”
Section: Analysis Of Capital Structure: Resultssupporting
confidence: 90%
“…This is true for firms incorporated both in the Euro area and outside it. However, Euro area firms seem to rely less on internal funds, more on debt and less on equity than firms based in countries not adopting the common currency, consistently with the findings of Muradoǧlu et al (2014).…”
Section: Analysis Of Capital Structure: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Claessens et al (2002) concluded from a sample of 77 countries, on one hand, that foreign direct investment is a complement and not a substitute of domestic stock market development, and on the other hand, that foreign direct investment is positively related with stock market capitalization and value traded. Muradoglu et al (2013) showed that small firms benefited from the European integration process not only by equity channel but especially through FDI flows. In light of this it is important to evaluate both variables as determinants of financing choices.…”
Section: Financial Liberalization and Foreign Direct Investmentmentioning
confidence: 99%
“…Modern trends in corporate finance management are associated with the globalization of the financial sphere and, as a consequence, the emergence of additional risks due to the increasing interdependence between the various structural elements of the financial market [6][7][8][9]. Therefore, there is a need to apply innovative methods of corporate finance management in order to promptly respond to changes in the external environment, while maintaining the focus of the company's development strategy [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%